Follow-up and reasons for extended-release naltrexone discontinuation for alcohol use disorder after hospital initiation - Marlene Martin; Manuel Seraydarian; James Gasper; Triveni DeFries (BMJ Open Quality)
Only 1.9% of the individuals in the USA with alcohol use disorder (AUD) receive medication for AUD. Hospitalisation presents an opportunity to identify patients with AUD and offer treatment. Extended-release naltrexone (XR-NTX) is a Food and Drug Administration-approved medication for AUD that reduces drinking days and heavy drinking days. XR-NTX can reduce healthcare costs, decrease acute care utilisation and increase retention in treatment. We offered and initiated XR-NTX during hospitalisation to patients with moderate-to-severe AUD. We describe the follow-up rates for XR-NTX after hospital initiation and the reasons for XR-NTX discontinuation in the outpatient setting after hospital initiation. We performed a retrospective chart review of 62 hospitalised patients with moderate-to-severe AUD who received XR-NTX between 1 November 2019 and 31 December 2020. Twenty-two patients (35.5%) received ≥1 dose of XR-NTX within the first 3 months of discharge, 22 (35.5%) stopped XR-NTX and 18 (29.0%) did not follow-up. Overall, 44 (71.0%) patients followed up after discharge. Among those that discontinued XR-NTX, the most common reasons were: (1) a preference for oral NTX; (2) clinicians switching patients to oral NTX after patients missed an XR-NTX dose; (3) clinician challenges in prescribing XR-NTX; and (4) patient obstacles to accessing outpatient care. Our study highlights several opportunities to address modifiable reasons to improve access to and retention in XR-NTX treatment.